"Yes, I'm the Doctor": One Department's Approach to Assessing and Addressing Gender-Based Discrimination in the Modern Medical Training Era. (November 2019) - McKinley, Sophia K.; Wang, Linda J.; Gartland, Rajshri M.; Westfal, Maggie L.; Costantino, Christina L.; Schwartz, Dana; Merrill, Andrea L.; Petrusa, Emil; Lillemoe, Keith; Phitayakorn, Roy
Abstract : While gender-based bias and discrimination (GBD) is known to exist in medical training, there is limited guidance for training programs on how to understand and combat this issue locally. The Massachusetts General Hospital Department of Surgery established the Gender Equity Task Force (GETF) to address GBD in the local training environment. In 2017, members of the GETF surveyed residents in surgery, anesthesia, and internal medicine at 2 academic hospitals to better understand perceived sources, frequency, forms, and effects of GBD. Overall, 371 residents completed the survey (60% response rate, 197 women). Women trainees were more likely to endorse personal experience of GBD and sexual harassment than men ( P < .0001), with no effect of specialty on rates of GBD or sexual harassment. Patients and nursing staff were the most frequently identified groups as sources of GBD. While an overwhelming majority of both men (86%) and women (96%) respondents either experienced or observed GBD in the training environment, less than 5% of respondents formally reported such experiences, most frequently citing a belief that nothing would happen. Survey results served as the basis for a variety of interventions addressing nursing staff and patients as sources of GBD, low confidence in formal reporting mechanisms, and the pervasiveness of GBD, including sexual harassment, across specialties. These results reproduce other studies' findings that GBD and sexual harassment disproportionately affect women trainees while demonstrating how individual training programs can incorporate local GBD data when planning interventions to address GBD. Abstract : Supplemental Digital Content is available in the text.